Constructing Religious Moderation through Language: A Comparative Study of Verses on Tawasut - Kamal, Helmi (Journal of Al-Tamaddun, 2025)
This study examines the linguistic construction of tawasut (religious moderation) in Qur’anic interpretation, focusing on how language shapes meaning in response to social realities. By comparing Tafsir al-Azhar and Tafsir al-Misbah, this research highlights how linguistic choices reflect differing understandings of moderation within Indonesian socio-religious contexts. The study addresses three key questions: (a) What are the objective representations of religious moderation in the tawasut verses within both tafsir works? (b) How is the meaning of tawasuth constructed in each text? and (c) What linguistic and contextual factors underlie the interpretive differences between them? Using qualitative linguistic analysis, the study investigates grammatical structures, semantic fields, and pragmatic interpretations of selected verses. Sixteen verses from twelve chapters were identified as central to the theme of tawasut, either textually through the root و-س-ط and its derivations or contextually, using related concepts such as al-ʿadl (justice), al-ḥasanah (virtue), and ṣirāṭ al-mustaqīm (the straight path). The findings categorise religious moderation into three domains: (1) balance and harmony, (2) justice and fairness, and (3) the middle-way as an alternative solution. Each domain reflects the socio-cultural and exegetical orientation of the commentators. This study demonstrates that linguistic interpretation not only reflects textual tradition but also responds to evolving societal needs. Language thus serves as a bridge between Qur’anic ideals and lived realities, offering a holistic and transformative understanding of moderation in a pluralistic society.